PENGAPLIKASIAN FACE PAINTING PADA TATA RIAS KARAKTER KERBAU DITINJAU DARI KEINDAHAN DAN KETEPATAN RIASAN - Dita Sari Pangestuti; Teti Kuswati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2021)
This research aims to find out the process of making make-up face painting buffalo characters. This type of research is qualitative research with descriptive methods. In this study, the author only describes the study's results as is and by the results of the panelist's assessment. The data collection method that the author uses consists of observation and documentation. The method of observation by observing the process of face painting with buffalo characters to models, equipped with the manufacture of buns and the wearing of buffalo character clothing. The study also used primary data sources and secondary data sources. Techniques for analyzing data using non-statistical data analysis with descriptive thinking patterns, namely by entering data obtained as is by the results of panelist assessments. Based on the results of observations and documentation carried out, it can be concluded that the make-up face painting of buffalo characters needs to be done in detail, taking into account time and fast movement so that it does not take a long time. In addition to paying attention to the time of work, it is also necessary to pay attention to aspects of beauty and total look